Proposição de um framework de análise de desperdícios segundo a perspectiva Lean em instituições de ensino superior - Schwantz, Patrícia Inês (2022)
The Lean management philosophy, through the proposal of continuous improvement, is centered on the pillars of creating value to the end user and reducing and eliminating waste. In Institutions of Higher Education (HEIs), the Lean philosophy enables improvements adding value for students, employees, and society, reducing costs and even reducing various forms of waste. However, it is noticeable that there is a theoretical gap in relation to the eight types of waste in HEIs and a lack of clear definitions about them (KLEIN et al., 2021). Thus, this research aims to propose a framework for analyzing the types of waste that occur in Higher Education Institutions. For this, the methodology proposed for this research is based on a qualitative-quantitative approach and, to validate the research instrument developed in this research, it was performed the evaluation by experts in the area through three methods: individual interviews, focus group and Delphi rounds. From the survey results, a consensus of the panel of experts was evident, approving 60 of the 83 questions. In general, the individual interviews and with the focal group of specialists made it possible to identify the content weaknesses in the initial bank of items presented to them and, through the Delphi rounds, each of the questions was evaluated as to their potential to measure the types of waste called constructs and to increment new or improve the questions presented. Therefore, one concludes that the use of the multiple triangulations of methods (individual interviews, focus group and Delphi method) allowed judging the relevance of different items to unequivocally gauge the types of waste in HEIs.